Stabilizing the Anode and Cathode Interface Synchronously via Electrolyte-Triggered Hydrogel Interphase for Zinc Metal Batteries - Cai, Xinze; Li, Xin; Liang, Jiahui; Qiu, Jiazhen; Lin, Wenkuo; Dai, Chunlong; Lin, Zifeng; Zhao, Jiangqi (Nano-Micro Letters, 2026)
The advancement of aqueous zinc metal batteries (ZMBs) is constrained by intrinsic interfacial issues in aqueous electrolyte systems. Here, using numerical simulation, we decipher the multi-scale causes of interfacial instability, elucidating the synergistic effect of macroscopic ineffective regions and microscopic passivation. Based on the analysis, we develop an electrolyte-triggered interphase construction strategy to resolve the interfacial failure. This strategy couples the in situ formation of hydrogel interphase on both the anode and cathode with the electrolyte filling process, thereby (1) facilitating contact between electrodes and the separator; (2) promoting anode reversibility through inducing a bilayer SEI that enhances Zn2+ desolvation kinetics and blocks electron tunneling; (3) ensuring long-term cathode cycling stability via restricting the irreversible dissolution of MnO2 and side-reactions. The resultant Zn metal anode exhibited a near-unity Coulombic efficiency (99.5%) for Zn plating/stripping at an extremely low current density of 0.1 mA cm−2 and the Zn/MnO2 full cell sustained 2000 full-duty-cycles with an exceptionally low decay rate of 0.0051% per-cycle. This work unlocks an alternative angle for promoting practical ZMBs toward more sustainable energy storage systems. Highlights: 1 Decipher the multi-scale causes of interfacial instability in aqueous electrolyte systems via numerical simulations. 2 Develop an electrolyte-triggered interphase construction strategy to achieve synergistic regulation of both the anode and cathode. 3 Achieve high Coulombic efficiency (99.5%) and long-term cycling stability (over 6000 h) at ultra-low current density (0.1 mA cm−2) in zinc metal batteries.